Direct combustion of wet/dry solution-impregnated cigarette butts for nano-FeOx synthesis: Effects of combustion conditions and NO reduction ability - Zhou, Zijian; Liu, Lei; Liu, Xiaowei; Zhou, Yue; Li, Chengpu; Peng, Dejun; Xu, Jingying; Wang, Changqing; Cao, Xiangkun Elvis (Colloid and interface science communications, 2022)
Cigarette butts (CBs) were used to synthesize nano-FeOx following a facile and rapid route. This method involves the impregnation of a nitrate solution with CBs and the adsorption of the precursors on the CBs. The wet or dried impregnated CBs were burned under the smoldering or flaming combustion mode to obtain nano-FeOx. This method differs from the cellulose-assisted combustion method as pure organic fuels are not used during the process. Excess energy is required for the sustenance of the combustion of impregnated CB, while the method of combustion of activated cellulose papers is self-sustaining. The physical and chemical characteristics of the nano-FeOx particles were determined under the combustion modes and whether they were dried or not. Flaming combustion of dry-impregnated CB could prepare nano-FeOx with good crystallization, while smoldering of wet-impregnated CB led to good low-temperature redox activities. [Display omitted] •Nano-FeOx was prepared by combustion of wet/dry solution-activated cigarette butts.•Smoldering and flaming combustion modes were considered.•FeOx prepared by smoldering combustion of wet samples had superior redox property.